Harmonization of Religious Life of Muslims and Non-Muslims in Peunayong Market, Banda Aceh City - Syifa Anindhita; Nurmahni Harahap; Halimatussakdiah Hasibuan (Journal of Aceh Studies, 2025)
Background of the problem: Conditions of religious diversity and non-Muslim perspectives in a Muslimmajority environment. Purpose: To determine the condition of inter-religious harmonization in Peunayong, Banda Aceh. Method: This research uses descriptive qualitative research methods with data collection through interviews, field observations, and documentation. After the data is obtained, the researcher will analyze the data with the following steps: data collection, data reduction, data display, and conclusion drawing and verification. Result: The results show that the condition of community harmonization has been running well so far, which can be proven by the attitude of tolerance. According to the research results, the condition of Peunayong Community harmonization is running very well.  Community harmony is well established due to tolerance and efforts to maintain diversity without causing conflict. Because basically Indonesian society is born with various diversities, according to the theory that Indonesia is a pluralistic country. Implication: Based on the results of the study, it shows that non-Muslims and Muslims in Peunayong have strong harmony. There is no conflict between religious communities and live side by side despite differences and diversity.